Synthesis and biodistribution studies of 99mTc labeled fatty acid derivatives prepared via "Click approach" for potential use in cardiac imaging. (30th September 2018) - Das, Soumen; Mathur, Anupam; Sakhare, Navin; Mallia, Madhava B.; Sarma, Haladhar Dev; Sachdev, Satbir Singh; Dash, Ashutosh
Abstract : 123 I‐Iodophenylpentadecanoic acid (IPPA) is a metabolic agent used in nuclear medicine for diagnosis of myocardial defects. Efforts are underway worldwide to develop a 99m Tc substitute of the above radiopharmaceutical for the aforementioned application. Herein, we report synthesis and biodistribution studies of 99m Tc labeled fatty acids (8, 11, and 15 carbons) obtained via "click chemistry" for its potential use in myocardial imaging. ω‐Bromo fatty acids (8C/11C/15C) were synthetically modified at bromo terminal to introduce a heterocyclic triazole with glycine sidearm in a five step procedure. Modified fatty acids were subsequently radiolabeled with preformed [ 99m Tc(CO)3 ] + synthon to yield the desired fatty acid complexes which were evaluated in Swiss mice. All the radiolabeled complexes were obtained with radiochemical purities >80%, as characterized by HPLC. Biodistribution studies of all three complexes in Swiss mice showed myocardial uptake of ~6‐9% ID/g at 2 minutes post‐injection, close to * I‐IPPA (~9% ID/g). Complexes exhibited significant retention in the myocardium up to 30 minutes (~1% ID/g) but were lower to the standard agent (~7% ID/g). Similar uptake of activity in myocardium for the newly synthesized complexes in comparison to 125 I‐IPPA along with favorable in vivo pharmacokinetics merits potential for the present "click" design of complexes for myocardial imaging. Abstract : 123 I‐Iodophenylpentadecanoic acid (IPPA) is a metabolic agent used for diagnosis of myocardial defects. Herein, we report 99m Tc‐labeled fatty acids (8, 11, and 15 carbons) obtained via "click chemistry" as a rationale substitute. ω‐Bromo fatty acids were synthetically modified at ω terminal and radiolabeled via [ 99m Tc(CO)3 (H2 O)3 ] + synthon. Biodistribution of complexes in Swiss mice showed myocardial uptake similar to*I‐IPPA at 2 min pi with favorable in vivo pharmacokinetics which merits potential for the present "click" design of complexes for myocardial imaging.